Kebijakan Kriminal dalam Menanggulangi Kejahatan Kesusilaan Melalui Internet - Muliadin, Mus; Aryani, Fajar Dian; Indriasari, Evy; Pratama, Erwin Aditya (Diktum: Jurnal Ilmu Hukum, 2020)
The development of cybercrime as a new form of crime in the cybersex world has been galvanized globally as a dark shadow of technological advances in the field of communication and information. because it allows for new forms of exploitation, new opportunities for criminal activity, and even new forms of crime. One of the cybercrime problems that is also very troubling and gets the attention of various circles, is the cybercrime problem in the field of decency. The research approach uses a normative juridical approach, the data consists of secondary data obtained through literature studies, and the data is analyzed analytically. Cybersex is a new form of adultery so clear legal arrangements are needed to be able to anticipate it. In addition to these penal efforts, non-penal (integral/systemic) should be put forward to overcome cybersex. Cybersex can be done by law enforcement with the positive laws that exist at this time by carrying out legal construction. Besides, the regulation by Positive Law of Indonesia is still spread in various laws and regulations and there are still some shortcomings so that in the future anticipatory policies of criminal law must be dating.